Formulation and Evaluation of Herbal Shampoo (International Journal of Scientific Research in Science and Technology, 2025)
The objective of this study is to formulate and evaluate poly-herbal shampoo for cosmetic purpose from herbal ingredients. Hibiscus powder, Neem powder, Henna powder, Amla powder, Shikakai powder, Ritha powder, Alo-vera gel was procured from local market in powdered form and rice water prepared by homemade method, then prepared decoction of these ingredients and mixing with each other and evaluated for its organoleptic and physicochemical characteristics. Herbal shampoo is used to cleansing of the hair also conditioning, smoothing, of the hair surface, good health of hair, hair free of dandruff, dirt grease and lice above all, its safety benefits are expected. The advantage of herbal cosmetics is their non-toxic nature, reduce the allergic reactions and usefulness of many ingredients. That’s why in present work we found good properties for the herbal shampoo and further optimization study benefits of herbal shampoo on human use as cosmetic product.
Keywords: Cosmetic; Herbal; Formulation; Evaluation